Ways Representing Metaphors in Translation (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The paper substantiates the need for a careful approach to choosing a method of translating metaphors in the political text, discusses the current methods of interlanguage transmission of metaphors identified in the study of modern English-language political texts and their translations into Russian, and also provides a number of recommendations for translators.